6(2x-4)=3(4x-22)

Simple and best practice solution for 6(2x-4)=3(4x-22) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2x-4)=3(4x-22) equation:


Simplifying
6(2x + -4) = 3(4x + -22)

Reorder the terms:
6(-4 + 2x) = 3(4x + -22)
(-4 * 6 + 2x * 6) = 3(4x + -22)
(-24 + 12x) = 3(4x + -22)

Reorder the terms:
-24 + 12x = 3(-22 + 4x)
-24 + 12x = (-22 * 3 + 4x * 3)
-24 + 12x = (-66 + 12x)

Add '-12x' to each side of the equation.
-24 + 12x + -12x = -66 + 12x + -12x

Combine like terms: 12x + -12x = 0
-24 + 0 = -66 + 12x + -12x
-24 = -66 + 12x + -12x

Combine like terms: 12x + -12x = 0
-24 = -66 + 0
-24 = -66

Solving
-24 = -66

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 4a+3=-9 | | p^2-10p-15=0 | | 3t-18=4t-16 | | 6x-2=70 | | -498=6(9x+16) | | 20=-3x+7(-2x+25) | | -7(x+8)-44=3-61 | | 8x^3-336x^2+2760x+1608= | | 2(7-3x)+1=2x-1 | | (3x+4)(x-3)=10 | | 8+-176=-72 | | 567=-6(10x-16) | | 8+176=-72 | | (x-8)*(x-8)-18=-2 | | 4k-7=2+k | | 504=-16x^2+484 | | 2(g-2)-4=3(g-3) | | 209-3x=33x+21 | | 75-6x=12x+15 | | 3+5d=11+4d | | 6x-7=3x-11 | | 9(2x+14)-4(3x+17)=64 | | -3x+6=18 | | 3x^2-27x=-2x^2-9x-16 | | 5.50+4.00(486-a)=2416 | | -486=6(7x-11) | | 7-8x=47-22x | | 3x-5=5x+12 | | 4(5y-4)=12y | | -61*3=x | | -120=-4(7x+9) | | 5y-9=7y-13 |

Equations solver categories